Chinese as a Second Language Multilinguals$1 (BSpeech Competence and Speech Performances Cognitive, Affective, and Sociocultural Perspectives - Sun, Peijian Paul.; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2020)
This book offers a comprehensive and systematic review of multilingual L2 learners$1 (Bspoken Chinese, focusing on the dual dimensions of speech competence and speech performance. Specifically, by adopting a mixed-methods approach, it explores the cognitive, affective, and socio-cultural differences between intermediate and advanced multilingual learners$1 (BL2 Chinese speech competence and speech performance. Drawing on a theoretical framework underpinned by the affective filter hypothesis, L2 willingness to communicate model, L2 motivational self-system, and L2 speech production models, this book not only contributes to our theoretical understanding of the roles of various factors in L2 Chinese speech competence and speech performance, but also offers practical insights into the implications for both teachers and learners in terms of how to minimize the gap between these two dimensions among L2 Chinese learners. It concludes with a discussion on the limitations of L2 Chinese speech and on future directions for the field. .s
Chapter 1: Introduction -- Chapter 2: Theoretical and conceptual frameworks -- Chapter 3: Speech competence and speech performance: A literature review -- Chapter 4: L2 learning and speaking: A literature review -- Chapter 5: Research design and methodology -- Chapter 6: Quantitative results and discussion -- Chapter 7: Qualitative results and discussion -- Chapter 8: Conclusion, implications, limitations, and recommendations.
Keywords: Linguistics$1 (BMethodology.s; Language and languages$1 (BStudy and teaching.s; Applied linguistics; Research Methods in Language and Linguistics; Language Education; Applied Linguistics